Politics and trade in the Indian Ocean world : essays in honour of Ashin Das Gupta - Mukherjee,Rudrabsghu Ed. Subramanian,Lakshmi Ed (Oxford University Press, 1998)
Chiefly on the organization of mercantile networks between the ocean and the hinterland states and the politics involved in it.